2005
DOI: 10.1111/j.0002-9092.2005.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk by Any Other Name … Consumer Benefits from Labeled Milk

Abstract: This article uses revealed preferences of consumers to study the consumer benefits from rBST-free and organic labeled milk. The article specifies and estimates a quadratic AIDS demand system model for different milk types using US supermarket scanner data. The introduction of rBST-free and organic milk is used to estimate consumer benefits, which are decomposed into two components, competitive and variety effects. Results show significant consumer benefits from organic milk and to a lesser extent from rBST-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 14 publications
7
84
2
Order By: Relevance
“…The significant but unexpected sign of this effect might indicate that consumers do not focus on these attributes as much in the investigated time period as studies of earlier time periods concluded (e.g. Kiesel, Buschena, and Smith 2005;Dhar and Foltz 2005). This might be evidence of a limited attention span by consumers as the discussion about rBGH is not as present and recent anymore as in earlier time periods.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The significant but unexpected sign of this effect might indicate that consumers do not focus on these attributes as much in the investigated time period as studies of earlier time periods concluded (e.g. Kiesel, Buschena, and Smith 2005;Dhar and Foltz 2005). This might be evidence of a limited attention span by consumers as the discussion about rBGH is not as present and recent anymore as in earlier time periods.…”
mentioning
confidence: 86%
“…Focusing on organic milk, Glaser and Thompson (2000) identified price premiums as high as 103%, and high own-price elasticities for organic milk products. Dhar and Foltz (2005) used a quadratic, almost ideal demand system (AIDS) for differentiated milk types in combination with supermarket scanner data. They found significant consumer valuation of organic milk, and to a lesser extent, rBGH-free milk.…”
Section: Introductionmentioning
confidence: 99%
“…Glaser and Thompson (2000), through the use of scanner data, find that purchases of organic milk are very sensitive to changes in prices. Dhar and Foltz (2005) considered demand interrelationships for rBST-(bovine growth hormone) free milk, organic milk, and unlabeled (conventional) milk through the estimation of a Quadratic Almost Ideal Demand System (QUAIDS). The data indigenous to this analysis are weekly milk prices and sales for 12 U.S. cities over the period of March 9, 1997, to February 24, 2002.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The direction of the bias is difficult to ascertain. Based on the current literature on milk demand analysis, organic milk and rBST-free milk are complements while conventional milk and rBST-free milk are substitutes (Dhar & Foltz, 2005). Likewise conventional milk and soymilk are complements (Dhar & Foltz, 2004).…”
Section: Issues Of Price Endogeneitymentioning
confidence: 99%
“…Up to now, most studies have either looked at demand reactions on a composite level (e.g., Dhar & Foltz, 2005), without differentiating by format, or examined one single format only (e.g., Bell & Latin, 1998). Regarding analyses of multiple retail formats, some of the literature has dealt with market entry of mass merchandisers like Wal-Mart (Basker & Noel, 2007) or pricing strategies of firms such as everyday low-pricing (Shankar & Bolton, 2004), which is typically implemented by discounters.…”
Section: Introductionmentioning
confidence: 99%